KEBIJAKSANAAN SYARI’AT ISLAM DALAM BERBUSANA ISLAMI SEBAGAI PEMENUHAN HAK-HAK ANAK PEREMPUAN - Akbar, Eliyyil (Musawa Jurnal Studi Gender dan Islam, 2015)
Dressing in unwelcome contemporary fashion to mistakenly conceal one’s identity in the name  of beauty is one of the causal factors of moral degradation threatening our young generation. To establish their identity and charming personality, many young girls perform malfunction of what they should politely and proportionally wear for the sake of the latest mode and art although they have to break religious laws and teachings. To deal with this phenomenon, regions governed under Islamic law establish suitable fashion criteria and administer mild punishment to whoever violates the policy. Some opponents of the rule have voice protest against it, claiming that it violates women’s right to express their style through fashion. It is widely known that there are some ill-conceived policies stirring up violence against the human rights. However, some policies formulated by Islamic legal administers in Takengon, Central Aceh, have granted women the right to wear the fashion of their choice. Here, the author wants to impart the wisdom of Islamic law in setting down the rule on fashion and in giving young women their rights. The wisdom can act as guidance for lawmakers against the formulation of divisive policies violating human rights. The rule on Islamic fashion in this discussion is based on the Syafi’i teaching that women must cover up their entire body except for the face and the palms of the hands. The wisdom of the Islamic rule is that it reminds and urges young girls to confide in their parents to ensure that their existence as women is protected.